1999
DOI: 10.1159/000024610
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Thermal Comfort and Indoor Air Quality Aboard 43 Flights on Commercial Airlines

Abstract: This paper reports the results of thermal comfort and indoor air quality measurements aboard aircraft from 43 flights on commercial airlines with a duration of more than 1 h. The measurements were performed continuously during the whole flight (from the departure gate to the arrival gate), and the parameters monitored were temperature, relative humidity and carbon dioxide concentration. The results were then compared with the ASHRAE Standards for the thermal comfort (ASHRAE Standard 55-92) and indoor air quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 7 publications
(8 reference statements)
2
19
1
Order By: Relevance
“…The time course of the humidity during the flight, which was lowest at cruising altitude, was typical of those previously measured (Haghighat et al 1999;Lindgren 2003) and consistent with theoretical predictions (Arnold et al 2000). The minimum humidity of 22.7 % during the flight is higher than many maximum humidity measurements for other flights, such as those by O'Donnell et al (1991), Haghighat et al (1999), Lee et al (1999), andLindgren (2003).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The time course of the humidity during the flight, which was lowest at cruising altitude, was typical of those previously measured (Haghighat et al 1999;Lindgren 2003) and consistent with theoretical predictions (Arnold et al 2000). The minimum humidity of 22.7 % during the flight is higher than many maximum humidity measurements for other flights, such as those by O'Donnell et al (1991), Haghighat et al (1999), Lee et al (1999), andLindgren (2003).…”
Section: Discussionsupporting
confidence: 88%
“…A contributing factor to the relatively high humidity on the flight in this study may have been the relatively high temperatures, which had a mean of 27.2°C. These temperatures are higher than that found in any aircraft by Haghighat et al (1999) and more than the mean value found by O'Donnell et al (1991). Given that most of the moisture in the cabin is from perspiration of the passengers (O'Donnell et al 1991;Arnold et al 2000) the high temperatures on the flight may have led to relatively higher humidity through greater perspiration.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…8 The paper examines the ways in which one pioneer of commercial jet flight, B.O.A.C., responded to the aeromedical implications that the increased size, speed, 4 On which see Bushnell 1960;Gibson and Harrison 1984;Hanrahan 1952Hanrahan , 1958Peyton 1968;and Robinson 1973;and Pascoe 2003;Adey 2010. 5 See Brundrett 2001;Carruthers et al 1976;Haghighat et al 1999;Hinninghofen and Enck 2006;House of Lords 2000Reid et al, 1986Reid et al, , 2006Jacobson 1975, 1976;Strøm-Tejsen et al 2008;Sudoł-Szopińska et al 2007;Whittingham 1953Whittingham , 1955 Coker and Ingram 2006;Cowling et al 2010;Garoon andDuggan 2008. 7 Bissell 2009;Caplan 1995;Erichsen 1867;Ferrari 2010;Harrington 2003;Keller andChappell 1996.Bennett 1928;Desnoes 1926.…”
Section: Introductionmentioning
confidence: 99%